Pemeriksaan Golongan Darah bagi Masyarakat di Dusun Wambasalahin, Kecamatan Lolong Guba, Kabupaten Buru, Provinsi Maluku - Imelda de KOCK; Yuniasih M.J Taihuttu; Halidah Rahawarin; Rachmawati D Agustin; Yisman F Makatita; Johan W Lepertery; Anugerah far-far; Dicky J Payung; Wanda Tanamal; Distance B. Maatita; Nathalia J.J. Resimery (Jurnal Mandala Pengabdian Masyarakat, 2026)
Blood typing is an essential procedure in hematology and blood transfusion to prevent fatal transfusion reactions and support medical diagnosis. However, in remote areas such as Wambasalahin Hamlet, Lolong Guba, Buru Regency, access to basic healthcare services remains limited, resulting in many residents being unaware of their own blood type. This activity aimed to provide knowledge and blood typing services to the community of Wambasalahin Hamlet, as well as to determine the distribution of blood groups and Rhesus (Rh) factors in the area. The examination was conducted using the slide test method with anti-A, anti-B, anti-AB, and anti-D antisera. Capillary blood samples were aseptically collected from the fingertip, and agglutination reactions were directly observed under adequate lighting. The results showed that blood group O (35.1%) was the most dominant, followed by group A (32.7%), AB (21.4%), and B (10.7%). The Rhesus positive (Rh?) factor was found in 62.5% of participants, while Rhesus negative (Rh?) accounted for 37.5%. These findings may serve as the foundation for establishing a blood group database in remote regions to support medical preparedness. The implementation of this activity ran smoothly with high community enthusiasm. Conclusion: Blood group O with a positive Rhesus factor was the most prevalent type found in Wambasalahin Hamlet. This activity increased community awareness of the importance of knowing one’s own blood type and may serve as a basis for establishing a blood group database to support healthcare services in remote areas.